Selective Brand Talkedness in Capital Market Consulting SMEs: The Case of Cakrawala Meta Askarah (CMA) - Ocan Ocan (Jobmark: Journal of Branding and Marketing Communication, 2022)
Unlike consumer products that thrive on mass-market exposure, capital market consulting services operate in a niche, highly regulated, and trust-dependent environment where branding strategies must be more relational than promotional. This study investigates how brand talkedness is constructed and sustained by Cakrawala Meta Askarah (CMA), a small consulting enterprise, through an interpretive case study using in-depth interviews with its founder. Guided by the six dimensions of brand talkedness (ranging from brand mention to brand’s top-of-talk), the analysis reveals that CMA’s brand presence is not amplified through social media campaigns but rather through service experience, professional trust, and networks among corporate secretaries, directors, and supporting capital market professionals. The findings highlight that selective, relationship-based conversations generate deeper brand resonance than conventional exposure-driven approaches, positioning brand talkedness as a strategic asset in specialized professional services. Theoretically, this research extends the brand talkedness framework into the domain of regulated consulting services; practically, it underscores the value of relational branding for SMEs seeking credibility and influence in trust-sensitive markets.